PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA, LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. NAVYA RETAIL INDONESIA - Pratama, Stiven Fransisco; Nurhadi, Mochamad; Rithmaya, Chitra Laksmi; Setiawan, Nurcholis (Buletin Studi Ekonomi; VOLUME.28.NO.01.TAHUN.2023DO - 10.24843/BSE.2023.v28.i01.p10, 2023)
The research objective was to examine the effect of leadership style, work discipline and work environment on employee performance. The sampling technique uses a saturated sample with a total of 73 employees at PT. Navya Retail Indonesia Surabaya Branch. The analysis technique used is multiple regression analysis. The results showed that leadership style had a significant positive effect on employee performance, while work discipline had no significant positive effect on employee performance, and the work environment had no significant positive effect on employee performance. The implications of this research for PT. Navya Retail Indonesia is paying attention to aspects of leadership style in order to improve the performance of its employees